2016
DOI: 10.1590/1414-431x20165253
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral brain-derived neurotrophic factor is related to cardiovascular risk factors in active and inactive elderly men

Abstract: Regular exercise plays an important preventive and therapeutic role in heart and vascular diseases, and beneficially affects brain function. In blood, the effects of exercise appear to be very complex and could include protection of vascular endothelial cells via neurotrophic factors and decreased oxidative stress. The purpose of this study was to identify the age-related changes in peripheral brain-derived neurotrophic factor (BDNF) and its relationship to oxidative damage and conventional cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…Accordingly, Radak et al [281] showed that levels of 8-Oxoguanine (8-oxoG) in old inactive individuals are higher compared to their active counterparts, indicating that regular physical activity promotes an adaptive response that involves a more efficient antioxidant defense mechanism and DNA repair machinery. Interestingly, elderly inactive men exhibit significantly higher oxLDL and lower total plasma antioxidant status (TAS) compared to either young inactive or elderly active group [32]. In a recent work by Park and Kwak [176], there was no difference in resting oxidative stress levels and antioxidant capacity between untrained and trained (RE and endurance trained athletes) young men, however, the untrained ones exhibited significantly higher MDA and PC levels following an acute bout of exercise compared to trained ones.…”
Section: Physical Inactivity and Oxidative Stress In Cardiovascular Dmentioning
confidence: 93%
See 4 more Smart Citations
“…Accordingly, Radak et al [281] showed that levels of 8-Oxoguanine (8-oxoG) in old inactive individuals are higher compared to their active counterparts, indicating that regular physical activity promotes an adaptive response that involves a more efficient antioxidant defense mechanism and DNA repair machinery. Interestingly, elderly inactive men exhibit significantly higher oxLDL and lower total plasma antioxidant status (TAS) compared to either young inactive or elderly active group [32]. In a recent work by Park and Kwak [176], there was no difference in resting oxidative stress levels and antioxidant capacity between untrained and trained (RE and endurance trained athletes) young men, however, the untrained ones exhibited significantly higher MDA and PC levels following an acute bout of exercise compared to trained ones.…”
Section: Physical Inactivity and Oxidative Stress In Cardiovascular Dmentioning
confidence: 93%
“…CVD and endothelial dysfunction are characterized by a chronic inflammatory response and oxidative stress [31,32]. Oxidative stress is the driving force in the pathogenesis and Furthermore, numerous reports are indicate that ROS act as a stimulator of inflammation [17][18][19][20].…”
Section: Oxidative Stress and Cardiovascular Diseasementioning
confidence: 99%
See 3 more Smart Citations